From Allostatic Load to Allostatic State—An Endogenous Sympathetic Strategy to Deal With Chronic Anxiety and Stress? - Ullmann, Enrico; Perry, Seth W.; Licinio, Julio; Wong, Ma-Li; Dremencov, Eliyahu; Zavjalov, Evgenii L.; Shevelev, Oleg B.; Khotskin, Nikita V.; Koncevaya, Galina V.; Khotshkina, Anna S.; Moshkin, Mikhail P.; Lapshin, Maxim S.; et al. (Frontiers in Behavioral Neuroscience, 2019)
The concepts of allostatic load and overload, i.e. a dramatic increase in the allostatic load that predisposes to disease, have been extensively described in the literature. Here, we show that rats engaging in active offensive response (AOR) behavioral strategies to chronic predator scent stress (PSS) display less anxiety behavior and lower plasma cortisol levels versus rats engaging in passive defensive response (PDR) behavioral strategies to chronic PSS. In the same chronic PSS paradigm, AOR rats also have higher lactate and lower glutamate levels in amygdala but not in control-region hippocampus versus PDR rats. The implications of these findings for regulation of allostatic and stress responses, and post-traumatic stress disorder (PTSD) are discussed.